2019
DOI: 10.1038/s41598-019-53966-w
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the aggregation and spatial organization of the vector of Chagas disease, Triatoma infestans, by the parasite Trypanosoma cruzi

Abstract: Triatominae insects are vectors of the parasite Trypanosoma cruzi, the etiological agent of Chagas disease affecting millions of people in Latin America. Some species, such as Triatoma infestans, live in the human neighborhood, aggregating in walls or roof cracks during the day and going out to feed blood at night. The comprehension of how sex and T. cruzi infection affect their aggregation and geotaxis is essential for understanding their spatial organization and the parasite dispersion. Experiments in labora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Although several studies show the effect of T. cruzi on behavioral changes [53,[61][62][63][64][65], so far, no study has analyzed whether there are differences in the olfactory physiology between infected and non-infected and a possible correlation of behavioral changes with their AP. In this context, it is possible to ask if the behavioral changes may be due to the AP modi cation in infected insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies show the effect of T. cruzi on behavioral changes [53,[61][62][63][64][65], so far, no study has analyzed whether there are differences in the olfactory physiology between infected and non-infected and a possible correlation of behavioral changes with their AP. In this context, it is possible to ask if the behavioral changes may be due to the AP modi cation in infected insects.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of these modi cations as a characteristic of an association between T. cruzi and triatomines could be the consequence of different adaptive or nonadaptive scenarios (e.g., adaptive host manipulation) [50][51]. While several works have analyzed the mechanisms associated with T. cruzi-vector dynamics (e.g., biotic and abiotic factors) to understand the T. cruzi-triatomine interactions, under a co-evolutionary scenario [52], literature about how the parasites may in uence the insects is more limited, and the studies have only been focused on the parasite's effects on four patterns of the vector's behavior: life-history traits, feeding, defecation, and dispersion/locomotion [53]. Different studies have found negative effects of T. cruzi infection on vector's survival [54][55][56][57], fecundity [57,58], post-embryonic development [57,59,60], behavior [53,[61][62][63][64][65], and physiological processes [54,58,[66][67][68], while other studies have not identi ed these effects on patterns of alimentation/defecation [54,69], development and reproduction [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…First, there will always be limitations in what the data generated in laboratory conditions can reveal about insect behavior in the field. Insects are submitted in the field to daily environmental oscillations of light, humidity and temperature, as well as vector aggregation that might shape different activity patterns from those observed in laboratory settings [58,78,79]. Moreover, laboratory-reared insects can lose the genetic variability observed in the field, probably due to inbreeding and stochastic processes such as founder effects and, thus, do not completely represent field populations [80].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of T . cruzi infection on triatomine behavior are scarcely investigated and the few studies available focused on fitness parameters, feeding-excretion behavior, aggregation/geotaxis and dispersion/locomotion (reviewed in [ 21 ],[ 58 ],[ 24 ],[ 29 ]). Feeding and excretion are behavioral parameters of paramount importance, since they determine the efficiency of T .…”
Section: Discussionmentioning
confidence: 99%
“… 113 In the laboratory, levels of negative geotaxis and aggregation are higher in both female and male adults of T. infestans infected with T. cruzi . 114 Comparing the ecological niches of seven Mexican triatomine species, the ecological niche used by T. cruzi -infected populations is often reduced in comparison to uninfected populations, perhaps caused by an effect of T. cruzi on insect fitness. 115 …”
Section: Effects Of T Cruzi On Triatominesmentioning
confidence: 99%